Examination of legal frameworks for town and urban planning and housing in Nigeria (2019)
This paper seeks to examine the legal frameworks for town and urban planning and housing policies in Nigeria. The questions which this paper will interrogate among others are: What are the Nigerian urban and housing problems? What legal instruments are put in place to curb these challenges? What are the impact of the existing legal instruments on the quest for affordable shelter in Nigeria? To achieve the objective of this paper, the paper adopts analytical research methodology and places heavy reliance on library and internet sources for information to identify the various challenges confronting Nigerian urban planning, development and housing needs. The paper reviews relevant legal instruments on urban planning and housing. The paper observes that a careful examination of urban and housing policies in Nigeria revealed potentialities without meaningful impact on the physical development of the country and availability of affordable shelter to Nigerians. Part of major draw-back in the implementation of physical urban development and housing policies is attributable to the level of public participation in the process of the decision making. Thus, the principles and goals of these policies were not internalized by members of public for whom they have been designed. The paper concludes with recommendations among others for a political will on the part of government to checkmate administrative bottlenecks working against the realization of Physical Urban Development and National Housing Policies objectives. Workable solutions should also be developed to internalize urban and housing policies through educational tools such as Information and Communication Technology and Social Media in combating urban planning and housing challenges in Nigeria.